A Case Study of Extension in Florida. (March 2016) - Gutter, Michael S.
Abstract : The purpose of this article was to describe the role of Extension in Florida. Because Florida is diverse in geography, population, industry, and income, the challenges include low‐wage jobs, income inequality, and food insecurity. Opportunities for Extension in Florida include collaboration with other organizations, the use of volunteers, innovative programming, and diverse opportunities for funding.